Recommendations to the probabilistic strength estimation of normal sections of the roadway bridge plate-gilled system - Shinder, V. K.; Volotsiuga, V. V.; Shinder, Yu. V. (Видавництво Львівської політехніки, 2013)
In this article are presented the basic general approach principles to the development of the technique for deformation resistance calculation of the defective span bridge construction in a probabilistic formulation, based on th e method of statistical testing operations. Подано основні положення загального підходу до побудови методики деформаційного розрахунку міцності дефектної прогонової мостової споруди в ймовірнісній постановці, яка базується на методі статистичних випробувань.
Keywords: probabilistic estimation; plate-gilled system; roadway bridge; normal distribution law; ймовірнісна оцінка; плитно-ребриста система; автодорожній міст; нормальний закон розподілу